Perilaku Merokok Pada Masyarakat Dan Implementasi Kebijakan Kawasan Tanpa Rokok (Ktr) Di Desa Ajung Kecamatan Kalisat Kabupaten Jember - Prehatin Trirahayu Ningrum; Reny Indrayani (Politeknik Negeri Jember, 2017)
Smoking behavior has become an important issue of public health around the world since the last decade. Indonesia is one of the developing countries which has the highest level of cigarette consumption and production. A large number of studies have shown that smoking behavior can cause adverse effects for health, but conversely, the number of smokers increased every year. Nowadays, the trend of smoking behavior has entered the category of younger age between 13 – 15 years old. The purpose of this research is to obtain a description about smoking behavior on people and about the implementation of “no-smoking area” policy in Ajung village, Kalisat district of Jember. This study uses a descriptive research design with observation method. This study was conducted in May 2014. The sample in this study is 56 peoples and 4 elementary schools. Variables researched in this study are the knowledge of smoking adverse effect, smoking activity, the age of first smoking experience, the number of cigarette smoked per day, and “no-smoking area” policy. The results of the study have shown that 60,87% respondents have knowledge about smoking adverse effect toward respiratory disorders, respondents who have smoked daily activity are about 19.64%, the majority of respondents start smoking at age of 15-19 years, the average of respondents smoking as many as 13 stems in a day, and only 2 elementary schools that disposed to implement the “no-smoking area” policy in their institution. Based on these results, it is recommended the more intensive counseling about the hazards and the adverse effects of smoking behavior from various related institutions (health services, social services). Local governments is suggested to make regulations which aims to implement policy about “no-smoking area” in all institutions.